Dogma Antroposentrisme Pemicu Krisis Lingkungan dalam Pandangan Ekoteologi Seyyed Hossein Nasr - Siti Ulfiani; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This article applies descriptive qualitative research methods by applying library research techniques in collecting data. The results and discussion of this research are the excessive selfishness of humans in exploiting nature, triggering the birth of the dogma of anthropocentrism, in which humans think that everything belongs to humans only, which triggers human indifference to nature resulting in an environmental crisis. Nasr offers the concept of ecotheology, which emphasizes the harmonious relationship between God, nature and humans. This study aims to discuss the anthropocentrism dogma as a trigger for environmental crises in the ecotheological view of Seyyed Hossein Nasr. The result is that anthropocentrism is the background for the emergence of the environmental crisis, as a result of human rejection of seeing God as a real